The Malversations of Authorship - Current Status in Academic Community and How to Prevent It - Masic, Izet (Acta Inform Med, 2018)
AIM: Aim of article was to evaluate knowledge and practice of authorship issues among the academic population in the medical field. MATERIAL AND METHODS: Article has an analytical character and includes 69 academic workers (from the medical field, with the status of a regular employee of the Faculty of Medicine or a professional associate) who responded to the survey. RESULTS: Within the total number of respondents in the study, 34.8% of them were added as coauthors, although they did not have any input in the writing process. Even 47.8% of the respondents were under psychological pressure, that they have to add their superiors to the list of authors, though they did not have any contribution at any stage of the article preparation, while 29% of the respondents had a tacit agreement about mutual adding to the author’s list, and 36.2% added their superiors to the author’s list, in order that the first author would get a permission to publish the article in a certain journal. CONCLUSION: The relationship between the author, the mentor, the data processing person, the person providing the moral support etc. must be established, and not all of them has a place in the list of authors, they should be given special places at the end of the article, a space for acknowledgments, where these people may be mentioned. The consciousness of the academic community must change for the purpose of the concrete progress of the academic community and the scientific contributions of its members.